Mobbing and discrimination against people with distabilities in the professional sphere - Chmurska, Edyta (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The first part of the article presents an outline of the discussed issues. The author cited definitions and attributes of minorities to illustrate the place of people with disabilities in society. They are part of the population and have their needs just like everyone else. They point to a very high importance of work in their lives, which not only allows them to meet their needs of material and living security but also self-realization. However, what they support above all is vocational rehabilitation. The work undertaken by people with disabilities as part of vocational rehabilitation should take into account the limitations and conditions resulting from their current state of health. The professional activity of people with disabilities is promoted by the media in the form of social campaigns. Nevertheless, despite intensive efforts, it does not bring the expected results. It should be noted that people with disabilities put up the barriers to employment themselves, these barriers are also put up by employers. Moreover, they are often victims of abuse and discrimination by employers, as evidenced by the statements presented in the article.